Irbesartan Prevents Metabolic Syndrome in Rats via Activation of Peroxisome Proliferator-Activated Receptor γ - Shinji Takai; Denan Jin; Mizuo Miyazaki (Elsevier, 2011)
Abstract.: Irbesartan, an angiotensin-receptor blocker, is a known agonist of peroxisome proliferator-activated receptor (PPAR) γ. In this study, thirteen-week-old spontaneously hypertensive (SHR)/NDmcr-cp rats, representing a genetic model of metabolic syndrome, were treated daily with placebo, irbesartan (30 mg/kg), valsartan (10 mg/kg), or pioglitazone (10 mg/kg) for 4 weeks. Significant reductions in systolic blood pressure were seen in the irbesartan- and valsartan-treated groups, but not in the pioglitazone-treated group. Compared with the placebo group, plasma insulin, homeostasis model assessment of insulin resistance index, and plasma triglyceride levels were significantly lower while plasma adiponectin levels were significantly higher in the pioglitazone- and irbesartan-treated groups, but not in the valsartan-treated group. Significant increases in the gene expression of adiponectin and GLUT4 within adipose tissue were also observed in the pioglitazone- and irbesartan-treated groups, but not in the valsartan-treated group. These findings suggest that through PPARγ stimulation along with angiotensin II inhibition, irbesartan may be an optimal treatment option in the prevention of metabolic syndrome as well as hypertension. Keywords:: angiotensin II, blocker, metabolic syndrome, peroxisome proliferator-activated receptor (PPAR) γ